The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise - Ceruzzi, Paul (Technology & Culture, 2011)
The article reviews the book “The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise” by Nathan Ensmenger.